2021
DOI: 10.1038/s41593-020-00773-6
|View full text |Cite
|
Sign up to set email alerts
|

Temporally distinct myeloid cell responses mediate damage and repair after cerebrovascular injury

Abstract: Cerebrovascular injuries can cause severe edema and inflammation that adversely affect human health. Here, we observed recanalization after successful endovascular thrombectomy for acute large vessel occlusion was associated with cerebral edema and poor clinical outcomes in patients who experienced hemorrhagic transformation. To understand this process, we developed a cerebrovascular injury model using transcranial ultrasound that enabled spatiotemporal evaluation of resident and peripheral myeloid cells. We d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
91
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(95 citation statements)
references
References 75 publications
2
91
0
Order By: Relevance
“…Whether this change in infarct sizes results in changes in disease recovery and tissue repair remains unknown. In a mouse model of meningeal cerebrovascular injury induced by transcranial ultrasound, blocking myeloid cell recruitment led to a lack of vascular repair and increased fibrosis in the injury site, suggesting that immune cell entry into vascular lesions is crucial for wound repair and that altering this process can lead to fibrosis 103 . The signals that lead to this fibrosis remain unknown.…”
Section: Cns Fibroblasts In Diseasementioning
confidence: 99%
“…Whether this change in infarct sizes results in changes in disease recovery and tissue repair remains unknown. In a mouse model of meningeal cerebrovascular injury induced by transcranial ultrasound, blocking myeloid cell recruitment led to a lack of vascular repair and increased fibrosis in the injury site, suggesting that immune cell entry into vascular lesions is crucial for wound repair and that altering this process can lead to fibrosis 103 . The signals that lead to this fibrosis remain unknown.…”
Section: Cns Fibroblasts In Diseasementioning
confidence: 99%
“…As resident microglia serve pro‐angiogenic effects in the brain (Brandenburg et al, 2016; Jiang et al, 2020; Mastorakos et al, 2021), we co‐stained Iba‐1 and isolectin B4 on brain sections of 9‐month‐old APP tg Myd88 fl/wt Cre +/− and APP tg Myd88 fl/wt Cre −/− mice and counted microglia with and without contact with blood vessels in CA1 area of the hippocampus (Figure 5f). We observed that haploinsufficiency of MyD88 significantly increased the distribution of microglia to blood vessels (Figure 5g; one‐way ANOVA followed by post‐hoc test, p <.05).…”
Section: Resultsmentioning
confidence: 99%
“…Aβ‐activated perivascular macrophages injure the neurovascular coupling through producing reactive oxygen species (Park et al, 2017). However, microglia were observed to serve pro‐angiogenic effects in brains with glioma, ischemia, or direct vascular injury (Brandenburg et al, 2016; Jiang et al, 2020; Mastorakos et al, 2021). Transcription of opn , vegf and igf1 genes in microglia is associated with angiogenesis (Jiang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This response is distinct from a single focal mTBI, during which a modest breach of the glia limitans superficialis is resolved by underlying microglia that project processes in a purinergic receptor–dependent manner and seal gaps between individual surface-associated astrocytes ( 13 , 23 ). Microglia processes can similarly stabilize the BBB and limit the extent of leakage following cerebrovascular injury ( 24 , 25 ). These reactions transpire within minutes of injury and depend on the well-described ability of microglia to detect extracellular ATP released from astrocytes via purinergic receptors like P2RY12 and P2RX4 ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for this discrepancy is that myelomonocytic cells can contribute to CNS damage and repair, depending on the time point after injury. For example, it was revealed in a model of cerebrovascular injury that robust myelomonocytic cell extravasation early after injury caused vascular breakdown and edema, but these same cells were required at later time points after injury to promote vascular repair ( 25 ). A similar scenario may unfold following mTBI.…”
Section: Discussionmentioning
confidence: 99%